SEMIK CODE IN SHORT STORIES SIAPA NAMAMU, SANDRA? WORKS OF NORMAN ERIKSON PASARIBU - Gesit Marti Bela; Imam Suhardi; Sri Nani Hari Yanti (Fakultas Bahasa dan Sastra Indonesia Universitas Jenderal Soedirman, 2023)
This research analyses a short story entitled Siapa Namamu, Sandra? by Norman Erikson Pasaribu. The story tells about the mourning journey of a mother after the death of her only child. This story contains psychological state of the main character and the atmospheric atmosphere, place, or object. Because of the reason, this research focuses on identifying lexias which categorized as semic code in Roland Barthes’ semiotic study. The method of this research is descriptive qualitative method. The data collection technique used is reading and note-taking. This research used content analysis as the data analysis technique. The result found there are 14 semic code lexias. With the psychoanalysis theory of Jacques Lacan, the meaning of those lexias can be categorized into 3 different meanings. There are happiness as demand, name as identity, and loss. The meanings describe the phase of incompleteness inside the main character’s self. In conclusion, the short story entitled Siapa Namamu, Sandra? can be used as a life lesson.